103 The ability of cardiogoniogmetry compared to flow fractional reserve at identifying physiologically significant coronary stenosis: the cardioflow study. (5th June 2017) - I Brown, Oliver; Clark, Andrew L; Chelliah, Raj; Davison, Benjamin; Mather, Adam N; Cunnington, Michael S; John, Joseph; Alahmar, Albert; Oliver, Richard; Aznaouridis, Konstantinos; Hoye, Angela
Abstract : Introduction: Cardiogoniometry (CGM) is method of 3-dimensional electrocardiographic assessment which has been previously shown to identify patients with angiographically defined, stable coronary artery disease (CAD). However, angiographic evidence of CAD, does not always correlate to physiologically significant CAD. The aim of our study was to assess the ability of CGM to detect physiologically significant coronary stenosis defined by fractional flow reserve (FFR). Methods: In a tertiary cardiology centre, patients with single vessel CAD were enrolled into a prospective double blinded observational study. A baseline CGM recording was performed at rest. A second CGM recording was then performed during the FFR procedure, at the time of maximal hyperaemia. A significant CGM result was defined as an automatically calculated ischaemia score<0 and a significant FFR ratio defined as<0.8. After enrolment, CGM and FFR results were compared and markers of diagnostic performance (sensitivity, specificity, positive predictive value and negative predictive value) were calculated at rest and during maximal hyperaemia. Statistical agreement between CGM and FFR was calculated by the Kappa statistic. Results: Forty patients were included (aged 61.1±11.0; 60.0% male), of which sixteen (40%) were found to have significant CAD when assessed by FFR. Markers of diagnostic performance of CGM are shown in the table. Conclusion: The diagnostic performance of CGM to detect physiologically significant stable CAD is poor at rest. Although, the diagnostic performance of CGM improves substantially during maximal hyperaemia, it does not reach sufficient levels of accuracy to be used routinely in clinical practice.